Role of information and communication technology in empowerment of women in Tamil Nadu - Janaki, V (International Journal of Engineering and Technology, 2018)
This study examines the impact of information and communication technology (ICT) on empowerment of women in Tamil Nadu. Infor-mation and communication technology has brought sweeping changes in the life of women. It has helped to break the shackles of slavery and facilitated greater empowerment of women. The present study has revealed that women using tablets, personal computers, internet con-nectivity, SMS, E-mail, Whats App, Facebook and internet browsing are more empowered socially, psychologically and intellectually than others. It is also found that use of ICT has increased the sense of self-worth and led to more social activism by women. It has also empow-ered women to make their own decisions on important aspects of their personal life such as education, employment, marriage, child birth etc. ICT has facilitated networking which make them aware of the job opportunities worldwide. ICT has increased the awareness about the law of the land which helps them to protect against injustice, discriminations and violence. ICT has integrated women with the society which has led to greater confidence and security.Â Â